Speech problem in cerebral palsy - HS, Anantha Murthy (Journal of All India Institute of Speech and Hearing, 1972)
The Orthopaedic Centre of Andhra Mahila Sabha at Madras is treating children suffering from Cerebral Palsy. Being a Rehabilitation Unit it has a team of medical and para-medical staff. At this Centre, a Cerebral Palsy Research and Demonstration Project has been sponsored by the Department of Health, Eduction & Welfare, Social and Rehabilitation Service, Washington, U. S. A., to study the effect of stereotaxic surgery in this condition. A speech therapy section was established in 1970 as a part of the Research Project. This paper analyses the speech problems that were encountered in Cerebral Palsy